Microlearning: instructional innovations in virtual education scenario - Salas Díaz, Fabiola; González Bello, Edgar Oswaldo; Estévez Nénninger, Etty Haydeé (IE Revista de Investigación Educativa de la REDIECH, 2021)
Microlearning refers to short, concise, often digital and mobile learning; due to its versatility in media and formats, as well as the possibilities of its application under different pedagogies, it represents an alternative of instructional innovation connected with Digital Era practices, demanded by virtual education in higher education scenarios. Therefore, the aim of this work was to understand the development of innovations in relation to the theoretical approaches used as analytical support of microlearning for virtual environments, differentiating the stages of the innovative process based on elements of reported scientific production knowledge. A documentary theoretical methodological approach was used aimed at compiling, analyzing and categorizing research under different innovation stages. Findings showed little use of theory to support research, although studies referring to an initial stage of innovation also stood out. At this stage contributions to empirical knowledge were on theoretical analyses and implementation models. It is concluded that the analysis and evolutionary perspective of microlearning advances present the bases to theoretically support instructional innovations, required from the students’ perspective, due to the growing technological interaction to which they are exposed.